The effect of an intermittent protocol on strength performance in female football players: an exploratory study - Alberto Pompeo; Everton Luis Rodrigues Cirillo; Paulo Cunha; José Vilaça-Alves; Júlio Costa; João Beckert; Diogo Simões; João Paulo Delgado; Filipe Casanova (Desafio Singular, 2023)
Football is a sport that involves a combination of continuous and intermittent effort. Therefore, players need to be able to recover quickly between moments of high intensity to continue to perform at a high level of output throughout the entire match. The present study aimed to evaluate the effect of an intermittent exercise protocol on the rate of high-intensive force production through the countermovement test (CMJ) in elite Portuguese female soccer players. The sample consisted of 12 players from the first division of women's football in Portugal (Age = 18.1 ± 0.9 years; Weight = 60.10 ± 5.8 Kg; Height = 1.63 ± 4.8 cm; BMI = 22.48 ± 1.5 kg/m2). The players performed an intermittent exercise protocol on a cycle ergometer, lasting 8 minutes, in which each minute corresponded to 40 seconds of high-intensity (4W/kg, based on the player's body weight) and 20 seconds of low-intensity (75W). Before and after the protocol, the players performed the CMJ. Through the results obtained, it was possible to observe that players presented a significant decrease in the height of the CMJ between the two moments (before- 29.92 ± 3.55cm vs after- 26.92 ± 4.05cm; p < 0.01). The present study allowed us to conclude that intermittent exercise protocol promoted a negative influence on CMJ performance.